Insights into the pathogenesis of catecholaminergic polymorphic ventricular tachycardia from engineered human heart tissue - Park, Sung-Jin (Circulation, 2019)
BACKGROUND: Modeling of human arrhythmias using induced pluripotent stem cell-derived cardiomyocytes has focused on single cell phenotypes. However, arrhythmias are the emergent properties of cells assembled into tissues, and the impact of inherited arrhythmia mutations on tissue-level properties of human heart tissue has not been reported. METHODS: Here, we report an optogenetically-based, human engineered tissue model of catecholaminergic polymorphic ventricular tachycardia (CPVT), an inherited arrhythmia caused by mutation of the cardiac ryanodine channel (RYR2) and triggered by exercise. We developed a hiPSC-CM-based platform to study the tissue-level properties of engineered human myocardium. We investigated pathogenic mechanisms in CPVT, by combining this novel platform with genome editing. RESULTS: In our model, CPVT tissues were vulnerable to develop reentrant rhythms when stimulated by rapid pacing and catecholamine, recapitulating hallmark features of the disease. These conditions elevated diastolic Ca(2+) levels and increased temporal and spatial dispersion of Ca(2+) wave speed, creating a vulnerable arrhythmia substrate. Using Cas9 genome editing, we pinpointed a single catecholamine-driven phosphorylation event, RYR2-S2814 phosphorylation by Ca(2+)-calmodulin-dependent protein kinase II (CaMKII), that is required to unmask the arrhythmic potential of CPVT tissues. CONCLUSIONS: Our study illuminates the molecular and cellular pathogenesis of CPVT and reveals a critical role of CaMKII-dependent reentry in the tissue-scale mechanism of this disease. We anticipate that this approach will be useful to model other inherited and acquired cardiac arrhythmias.